2017
DOI: 10.1007/s00402-017-2627-9
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Achilles tendon ruptures: is early functional rehabilitation daily routine?

Abstract: Our study shows that a huge variability in rehabilitation after Achilles tendon rupture exists. This study shows different strategies in rehabilitation of Achilles tendon ruptures using a convertible vacuum brace system. To improve patient care, further clinical as well as biomechanical studies need to be conducted. This study might serve as basis for prospective randomized controlled trials to optimize rehabilitation for Achilles tendon ruptures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 47 publications
1
25
0
7
Order By: Relevance
“…Combined with the novel primary outcome of return to sport included in this study, similar functional recovery was observed between surgical and conservative treatment group, even though surgical treatment was recommended owing to lower rerupture rate according to previous studies [37,38]. Moreover, conservative management accompanied with early weightbearing of the injured tendon was reported to be capable of stimulating collagen and healing process, leading similar re-rupture rate as surgical treatment [10,[39][40][41]. Collectively, a novel recommendation of more than just considering re-rupture and, conservative treatment with similar functional recovery as well as lesser complication on ATR might be considered if patients' status were suitable.…”
Section: Discussion Innovationsupporting
confidence: 68%
“…Combined with the novel primary outcome of return to sport included in this study, similar functional recovery was observed between surgical and conservative treatment group, even though surgical treatment was recommended owing to lower rerupture rate according to previous studies [37,38]. Moreover, conservative management accompanied with early weightbearing of the injured tendon was reported to be capable of stimulating collagen and healing process, leading similar re-rupture rate as surgical treatment [10,[39][40][41]. Collectively, a novel recommendation of more than just considering re-rupture and, conservative treatment with similar functional recovery as well as lesser complication on ATR might be considered if patients' status were suitable.…”
Section: Discussion Innovationsupporting
confidence: 68%
“…[21][22][23][24] Poor vascularisation negatively affects the inflammation that is essential for the restoration of the mechanical and biological properties of tendons during the healing process. 25,26 Ageing tenocytesthe dominant cell type in tendonstend not to be able to facilitate the proper differentiation of progenitor cells, resulting in ineffective healing. This leads to scar formation rather than tendon tissue regeneration, which results in reduced tensile strength.…”
Section: Healing Of the Tendon (Repair And Regeneration)mentioning
confidence: 99%
“…Although the cells themselves will experience a lower strain than the tendon fascicles (Screen, Lee, Bader, & Shelton, 2004), previous studies have indicated that tendon cells can change their gene expression and function in response to strain (Thorpe, Clegg, & Birch, 2010). As a gradual return to exercise plays an essential part of the rehabilitation programme in both horses and humans (Frankewycz et al, 2017; Ortved, 2018), it is critical to understand the effects of force on both the endogenous adult tendon cells and any cells that may be applied therapeutically to improve regeneration.…”
Section: Introductionmentioning
confidence: 99%